TATA KELOLA KOLABORATIF ANTARA KOMISI PEMILIHAN UMUM, BADAN PENGAWAS PEMILU, DAN PEMERINTAH DAERAH DALAM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH SERENTAK 2024 - Elfito, Fidya Arzita; Rahmawati, Rita; Apriliyani, Neng Virly; Wahyudin, Cecep; Purnamasari, Irma; Saprudin; Apriliani, Afmi; Ramdani, Faisal Tri; Hernawan, Denny (Jurnal Governansi, 2026)
The 2024 Simultaneous Regional Elections serve as a crucial momentum for the consolidation of democracy at the local level, including in Bogor Regency, one of the regions with the highest number of voters in West Java. Additionally, Bogor Regency is categorized as a medium-risk area in the Election Vulnerability Index according to Bawaslu reports, thus posing potential risks of horizontal conflict and technical challenges in the election process. This complexity requires collaborative governance across institutions to ensure a democratic, inclusive, and peaceful electoral process. This study aims to examine the forms, challenges, and efforts of collaboration among key actors such as the General Elections Commission (KPU), the Election Supervisory Board (Bawaslu), the National Unity and Politics Agency, the police, the media, and the community in organizing the Pilkada in Bogor Regency. A descriptive quantitative approach was employed, involving 145 respondents from institutions and the public using disproportionate stratified random sampling and simple random sampling techniques. Data were collected through observation, interviews, documentation, and Likert-scale questionnaires, and analyzed using the Weight Mean Score (WMS) method. The findings indicate that inter-agency collaboration has been running well, with an average score of 4.13 (institutional respondents) and 3.80 (community respondents). The dimensions of facilitative leadership and institutional design demonstrated the strongest performance, while the starting condition dimension was the weakest. These findings underscore the importance of strengthening initial capacity and developing clear collaborative Standard Operating Procedures (SOPs). The novelty of this research lies in the empirical application of the Collaborative Governance approach (Ansell & Gash, 2008) in the context of regional elections in a conflict-prone area, along with a structured analysis based on four main dimensions. This study implies the need for a sustainable collaboration system at every stage of the electoral process to establish a participatory, secure, and accountable government.